PENGGUNAAN GAME BASED LEARNING “EDUCAPLAY” SEBAGAI EVALUASI PEMBELAJARAN QIRO'AH DI PERGURUAN TINGGI MALANG: Penelitian Tindakan Kelas - Abdul Rohman Sudesi; Uril Bahruddin; Nur Hasan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe the game-based learning media educaplay as a learning evaluation tool in the classroom and the educaplay application, which is very fun, active, creative, and effective for improving student learning outcomes. This research is included in the quantitative category. Problem identification was carried out using the Classroom Action Research (PTK) approach by implementing two action cycles, and in each cycle, two learner process meetings were held. Each cycle consists of planning, implementation, observation, and reflection. Students work on questions that have been prepared in the educational media at each meeting. A total of 41 students in the PKPBA (Special Arabic Language Development Program) class at Maulana Malik Ibrahim Islamic State University, Malang, were research subjects. The results of the research explain that education as a learning medium is also a medium for evaluating students' learning processes. Eduacaplay media was obtained as a stimulus for students to understand the material presented so that they felt motivated, enthusiastic, happy, and active. The percentage in the educational media shows that student learning outcomes increased in the first cycle; the first meeting had a percentage of 12.20%, increasing in the second meeting to 26.83%. Then, the first meeting of the second cycle was 80.49%, and the second meeting increased to 95.12%. Most students achieve completeness in working on questions on educational media because they feel motivated, fun, and more active.